Thorns and Roses on the Preparation for Licensure Examination of Preservice Mathematics Teachers - Marvin B. Cortel; Stephen Raymund Jinon (PT FORMOSA CENDEKIA GLOBAL, 2024)
This Qualitative research was conducted in February 2023 among the Bachelor of Secondary Education Mathematics Major in a newly converted University in the Province of Iloilo. It aimed to determine the thorns and roses or the challenges and coping Mechanisms of 4th year Bachelor of Secondary Education Mathematics Major in Preparation for the licensure examination for teachers, a very important examination to be a licensed teacher in the Philippines and could help the students have a stable job after college. Data needed were gathered through interview. Thematic Analysis was used to analyze the data. The study revealed that there are 4 challenges the participants encountered during their preparation for the LET examination such as Family Status, Environment which incorporated for noisy surrounding, and Number of Concept to study and Low self-confidence. To cope with these challenges the respondents utilized social media platforms such as facebook as a review material and study material. The result shows that the respondents’ wants to enroll in a review center after they graduate to further enhance their learning. They faced many challenges and these may cause problem in there preparation for the licensure examination if it’s not controlled. Out of these problems, the school could provide program that would help them prepare more in the Licensure exam